Captain Kidd's Lost Ship : The Wreck of the Quedagh Merchant - Hanselmann, Frederick H. (Book collections on Project MUSE., 2019)
This book uses historical and archaeological evidence to identify the wreck of Quedagh Merchant and deconstruct the tales of the nefarious Captain Kidd. The analysis takes in the site's main features, wood samples from the hull, the hull's construction, and mass spectrometry of sampled ballast stones.